ANTIOXIDANT PROPERTY ON VARIOUS LEAF MATURITY OF PIPER SARMENTOSUM - Syafiq D.R., Ilyas; Ghazali, Nabilah; Dewi, Aptika; Jelita, Mega (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Piper sarmentosum known as Kaduk in Malaysia is a climbing herb with long runners comes from the family of Piperacaeae. Piper sarmentosum has been traditionally used in culinary and alternative medicines in different parts of the world to cure many diseases and ailments. Thus, this study aims to screen antioxidant activity of P. sarmentosum based on the leaf maturity, from young, middle-matured and matured leaf. First and foremost, the leaf will be extracted in 70% methanol and the antioxidant activity was determined by using Ferric Reducing Antioxidant Power (FRAP) assay. Result showed that the young leaves contain the highest antioxidant activity rather than middle-matured and matured leaves. Hence, if P. sarmentosum’s leaves are to be collected for its antioxidant properties, it is best to harvest the young leaves to gain the optimized yield of antioxidant properties.